Bee-pollen retailed in Tuscany (Italy): Labelling, palynological, microbiological, and mycotoxicological profile. (April 2021) - Nuvoloni, Roberta; Meucci, Valentina; Turchi, Barbara; Sagona, Simona; Fratini, Filippo; Felicioli, Antonio; Cerri, Domenico; Pedonese, Francesca
Abstract: Bee pollen is the result of flower pollen collecting and processing by honey bees. Due to its nutritional profile, it is considered a functional food. The present work aimed at evaluating labelling, pH, Aw, microbiological and mycotoxicological profile of 29 bee pollen samples (dried and fresh) purchased at retail in Tuscany (Italy). Only one pollen lacked more than two mandatory indications. Aw ranged from 0.19 to 0.77, while pH from 4.50 to 6.10. Fresh samples presented higher bacterial loads than dried samples. Total bacterial counts, Enterobacteriaceae, yeasts and molds and lactic acid bacteria ranges were 2.2–6.0, <2–4.1, <1–4 and <2–6.0 log CFU/g, respectively. Escherichia coli, Staphylococcus aureus, Bacillus cereus and sulphite-reducing clostridia loads were lower than the detection limit; Salmonella spp. and Listeria monocytogenes were always absent. As for mycotoxins, total aflatoxins were detected in all samples (5.2–34.4 μg/kg). Higher deoxynivalenol concentrations were detected (maximum: 179.7 μg/kg). Since the occurrence of spoilage microorganisms seems to be frequent, leading to possible alterations of the organoleptic profile, the microbiological quality of fresh bee pollen should be monitored. The risk related to the presence of pathogenic microorganisms seems to be very low, while attention must be paid to the presence of toxic metabolites. Highlights: Bacterial contamination of bee pollen can be high, especially in fresh samples. Presence of pathogenic microorganisms can be considered uncommon. Bee pollen contamination by mycotoxins must be considered. Mislabelled samples are present at retail level.